2004
DOI: 10.1021/jf035407c
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial Transport of Chlorogenic Acid, Caffeic Acid, and Their Colonic Metabolites in Intestinal Caco-2 Cell Monolayers

Abstract: Both chlorogenic and caffeic acids exhibited nonsaturable transport in Caco-2 cells, whereas caffeic acid also showed proton-coupled polarized absorption. Thus, the absorption efficiency of caffeic acid was greater than that of chlorogenic acid. Polarized transport of caffeic acid was inhibited by substrates of MCT such as benzoic and acetic acids. Almost all of the apically loaded chlorogenic and caffeic acid was retained on the apical side, and the transepithelial flux was inversely correlated with the parac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
187
2
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(211 citation statements)
references
References 49 publications
(100 reference statements)
19
187
2
3
Order By: Relevance
“…p-Coumaric acid was found to have a significant apical to basolateral transfer (37%) of p-coumaric acid, and a lower basolateral efflux (12%), which is consistent with previously published work (Konishi and Shimizu, 2003;Konishi and Kobayashi, 2004;Poquet et al, 2008). p-Coumaric acid is hydrophilic (Log P -0.65 (Luo et al, 2011)) and has a relatively low molecular weight (164).…”
Section: Transport Studysupporting
confidence: 90%
See 1 more Smart Citation
“…p-Coumaric acid was found to have a significant apical to basolateral transfer (37%) of p-coumaric acid, and a lower basolateral efflux (12%), which is consistent with previously published work (Konishi and Shimizu, 2003;Konishi and Kobayashi, 2004;Poquet et al, 2008). p-Coumaric acid is hydrophilic (Log P -0.65 (Luo et al, 2011)) and has a relatively low molecular weight (164).…”
Section: Transport Studysupporting
confidence: 90%
“…The degree of phenolic acid transport is associated with the extent of ionisation (Poquet et al, 2008); ionisation creates a concentration gradient across the intestinal cells allowing passive diffusion of the phenolic acid. It has also been proposed that facilitated transport of coumaric acid using a proton pump, which is only active across a concentration gradient (Konishi and Shimizu, 2003;Konishi and Kobayashi, 2004).…”
Section: Transport Studymentioning
confidence: 99%
“…These esterase activity are able to release cinnamic acid of CGA structure, which can then be absorbed and metabolized to its primary metabolites (caffeic acid, ferulic, isoferulic, and p-coumaric) (Couteau et al 2001). Additionally, Konishi et al (2004) demonstrated that CA liberated from CGA by intestinal mucosa esterase, is not only absorbed via paracellular diffusion but also actively absorbed by the monocarboxylic acid transporter www.ccsenet.org/cco Cancer and Clinical Oncology Vol. 1, No.…”
Section: Metabolism Absorption and Bioavailability Of Hydroxycinnamimentioning
confidence: 99%
“…kwasy: m-kumarowy, ferulowy i 3-hydroksyfenylopropionowy) mogą wnikać do komórek przy udziale białek transportowych z rodziny MCT (ang. monocarboxylic acid transporter) [19]. W komórkach nabłonka jelita i w wątrobie kwas kawowy ulega glukuronidacji przy udziale UDP-transferazy glukuronowej.…”
Section: źRódła Kwasu Kawowego I Jego Wchłanianie W Przewodzie Pokarmunclassified